(untitled) (Research, Society and Development, 2021)
Objective: to know the perception of nurses about the care and practices developed with women diagnosed with breast cancer. Methodology: this is a qualitative research, exploratory-descriptive, developed with nurses who work in the care of women with breast cancer. Data collection took place through semi-structured interviews, of an individual character, respecting the privacy of the participants. The data were analyzed through thematic content analysis proposed by Minayo. Ethical health principles were respected, in accordance with Resolution No. 466/2012. Results: from the analysis, two themes emerged: Nursing care for women with breast cancer: practices and confrontations; and, difficulties faced by women diagnosed with breast cancer, in the nurses’ voice. Final considerations: the importance of encouraging nurses to reflect on the care of women with breast cancer is perceived, in order to (re) think the assistance offered in the entire biopsychosocio-spiritual dimension of women.